ANALISIS STRATEGI KREATIF IKLAN @OURDAILYDOSEID #BABYIGOTYOURBAG DI INSTAGRAM VERSI BIJAK MENGGUNAKAN KANTONG PLASTIK KARYA PT.KHARISMA JINGGA KREASI - Alika Umaira Suhendro (2020)
ANALYSIS CREATIVE STRATEGY OF ADVERTISING @OURDAILYDOSEID #BABYIGOTYOURAG ON INSTAGRAM WISELY VERSION USING PLASTIC BAGS BY PT. KHARISMA JINGGA KREASI Alika Umaira Suhendro ABSTRACT This study discusses the advertising creative strategies used by PT. Kharisma Jingga Kreasi in @ourdailydoseid #BabyIGotYourBag ad on the wise version of Instagram using a plastic bag. This study aims to determine the implementation of creative advertising strategies carried out by PT. Kharisma Jingga Kreasi in the process of making the ad @ourdailydoseid #BabyIGotYourBag on Instagram so that people can be wiser in using plastic bags. The concepts used in this research are Creative Strategy, Advertising, and AIDCA Model. The research approach used in this study is a descriptive qualitative approach. Data collection methods used are case studies. Data collection techniques were carried out by means of interviews through the WhatsApp application with the speakers, namely the strategy team from PT. Kharisma Jingga Kreasi as key informant 1, the creative team of PT. Kharisma Jingga Kreasi as key informant 2, and Our Daily Dose Consumers as informant 1. The results obtained based on interviews conducted have shown that in determining a creative strategy to create an ad @ourdailydoseid #BabyIGotYourBag on Instagram, PT. Kharisma Jingga Kreasi has carried out the appropriate stages in determining the creative strategy. The determination of the creative strategy includes the stages of the creative process consisting of preparation and understanding of the problem, maturation of the problem, the discovery of ideas, and evaluation of ideas. Then the ad style uses a creative execution style that combines life footage and factual messages on the ad using the resonance advertising approach. These advertisements undergo information, persuasive, and reminder functions by using the appeal of emotional combination ads that lead to functional. The determined creative strategy for advertising is then implemented into the AIDCA Model. The conclusion of this research is the creative strategy in an advertisement must be able to answer the 5W + 1H elements, namely what, when, where, why, who, and how. In the advertisement @ourdailydoseid #BabyIGotYourBag on Instagram by PT. Kharisma Jingga Kreasi, all elements of 5W + 1H have been answered through a creative strategy that has been determined and successfully implemented in the ad. This ad does not highlight the advantages of Our Daily Dose shopping bags, but aims to provide awareness in the target audience so that it is wise to use plastic bags so that the element of conviction in the AIDCA Model is not fulfilled. Keywords: Advertising, Creative Strategies, Our Daily Dose, Plastics, PT. Kharisma Jingga Kreasi